A further assessment of a role for Toll-like receptor 4 in the reinforcing and reinstating effects of opioids. Issue 2 (April 2020) - Yue, Kai; Tanda, Gianluigi; Katz, Jonathan L.; Zanettini, Claudio
Abstract : The Toll-like receptor 4 (TLR4) antagonists, (+)-naloxone and (+)-naltrexone, have been reported to decrease self-administration of opioids in rats and to reduce other preclinical indicators of abuse potential. However, under the self-administration conditions studied, the effects of TLR4 antagonists were not reinforcer selective, questioning the involvement of those receptors and their mediated inflammatory response specifically in opioid abuse. The objectives of the current study were to further characterize the reinforcer specificity of TLR4 antagonism in opioid self-administration and to explore its effects in a preclinical model of craving/relapse. The TLR4 antagonist (+)-naltrexone decreased responding in rats trained to self-administer the µ-opioid receptor agonist remifentanil, but with a potency that was not significantly different from that observed in another group of subjects in which responding was maintained by food reinforcement. Responding reinstated by heroin injection was decreased by (+)-naltrexone; however, a similar reduction was not reproduced with the administration of another TLR4 antagonist, lipopolysaccharide from Rhodobacter sphaeroides, administered into the NAcc shell. Thus, TLR4 antagonists lacked reinforcer selectivity in reducing opioid self-administration and were not uniformly effective in a model of craving/relapse, suggesting limitations on the development of (+)-naltrexone or TLR4 antagonists as treatments for opioid abuse.